Impacts of wholesale electricity price under varying carbon price levels on carbon emissions and economic output in Australia - Rabindra Nepal; Nirash Paija (Asian Development Bank Institute (ADBI), 2020)
Reducing global carbon emissions and mitigating the adverse impacts of climate change is a fundamental environmental challenge. Australia's target is to reduce carbon emissions by between 26% and 28% by 2030 compared to 2005 emission levels. Carbon pricing can be an effective market-based instrument for reducing carbon emissions. This paper examines the impact of varying carbon price levels on carbon emissions by incorporating the different carbon price levels in the electricity prices and eventually employing time series econometrics based on an autoregressive distributed lagged (ARDL) model. We use quarterly data spanning the period 2001 Q3 to 2019 Q1 and undertake varying scenario analysis. First, we design a scenario with a low and high carbon tax where we test and confirm the existence of a long-run equilibrium relationship among economic output, wholesale electricity price, and emissions under the high carbon tax scenario based on cointegration relationships. Our empirical results reveal that a stable wholesale electricity pricing with a carbon price and carbon emission nexus exists in the long run where a 1% hike in wholesale electricity price under a high carbon price scenario reduces carbon emissions by 0.57%. The vector error correction modeling-based Granger causality test suggests the presence of a bidirectional causality among electricity pricing, carbon prices, and carbon emissions in the long run. Therefore, Australia needs to implement a carbon emissions mitigation scheme that places a high tax rate on polluters such as fossil-based electricity generators to achieve reduced emissions and a sustainable economy.
Keywords: Q54; P22; N57; C51; 330; carbon emissions; carbon prices; Australia; VECM Granger causality